Development of Learning Media (LKPD) Themes of Ecosystem Based on "Salingtemas" - Nora Rahayu; Ashar Hasairin; Daulat Saragi (Randwick International of Education and Linguistics Science Journal, 2023)
This study aims to develop LKPD Ecosystem themes to improve the ability of valid, practical, and effective science literacy. Learning products developed in the form of LKPD based on salingtemas. This type of research is Research and Development (R&D). With a 4-D development model. This study involved students in grade V SD Negeri 28 Bandar Baru as the subject of research. Data was collected using expert validation sheets, observation sheets of learning implementation, student response questionnaires, and scientific literacy capabilities tests. The data obtained is then processed and analyzed descriptively. The results showed that LKPD themed the ecosystem to improve the ability of students in the literacy based on salingtemas sciences developed was in the valid category and suitable for use. Based on the results of the trials conducted, it was found that LKPD had met the validity aspects. This can be seen from: 1) The implementation of learning in the initial trial is quite practical and the implementation of learning in the next trial is categorized as very practical; 2) Use of LKPD in Learning Natural Sciences Ecosystem Themes developed in terms of students' responses are classified as practical. LKPD based on salingtemas has also met the effectiveness aspects seen from the student science literacy capability test.